2020
DOI: 10.1016/j.gie.2020.03.1126
|View full text |Cite
|
Sign up to set email alerts
|

Sa1330 ECT2 PROMOTES PROLIFERATION AND METASTASIS OF ESOPHAGEAL SQUAMOUS CELL CARCINOMA VIA THE RHOA-ERK-VEGF/MMP9 SIGLING AXIS

Abstract: delayed subcutaneous emphysema treated with endoscopic clips. The median length of hospital stay was 2 (2-7). The average Eckardt score at follow up was 1.2 AE 1.8 (0-8). The average Eckardt score variation was-5.9 AE 3.5 (-10-4). Twenty-five patients (89%) had a reduction by 3 or more of the Eckardt score. There was no difference with the type of achalasia: type 1Z100% and type 2Z90%. Conclusion: Our data suggests that POEM is a promising procedure to improved patient with achalasia with a relatively low risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In addition to the suppression of MMP‐2 and MMP‐9, 50 μM of resveratrol was found to inhibit the phosphorylation of ERK and p38 (Figure 5a), thus blocking the activation of these two proteins. The activation of ERK had been reported to promote the metastasis capacity of cancer cells (Cai et al., 2020; Lv et al., 2020; Meng et al., 2020; Song et al., 2020; Sun et al., 2020) and p38 (Hong et al., 2020; Liu et al., 2019; Pan et al., 2020; Ramadoss et al., 2017; Zhang et al., 2020; Zhu et al., 2019). In addition, blocking the phosphorylation of ERK and p38 has been tested as an anti‐metastatic strategy in cancer treatment (Choi et al., 2019; Tang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the suppression of MMP‐2 and MMP‐9, 50 μM of resveratrol was found to inhibit the phosphorylation of ERK and p38 (Figure 5a), thus blocking the activation of these two proteins. The activation of ERK had been reported to promote the metastasis capacity of cancer cells (Cai et al., 2020; Lv et al., 2020; Meng et al., 2020; Song et al., 2020; Sun et al., 2020) and p38 (Hong et al., 2020; Liu et al., 2019; Pan et al., 2020; Ramadoss et al., 2017; Zhang et al., 2020; Zhu et al., 2019). In addition, blocking the phosphorylation of ERK and p38 has been tested as an anti‐metastatic strategy in cancer treatment (Choi et al., 2019; Tang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…ECT2 acts as an oncogene and is involved in the proliferation and metastasis of several tumors. Sun et al found that ECT2 was involved in the development of esophageal cancer through the RhoA-ERK signal pathway [ 25 ]. Zhi et al found that ECT2 promoted the proliferation of glioma cells by upregulating PTTG1 expression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In oral cancer, reducing the expression of ANLN can promote apoptosis and inhibit the proliferation, invasion and migration of cancer cells through PI3K/mTOR signal pathway [65]. ECT2 regulates the expression of vascular endothelial growth factor and MMP9 through RhoA-ERK signaling pathway, thus promoting cell proliferation, invasion, migration and tumor development [66]. ACADM can promote the EMT process of breast cancer cells and improve the migration and invasion ability of breast cancer cells [67].…”
Section: Austin Publishing Groupmentioning
confidence: 99%